2008
DOI: 10.1248/bpb.31.1723
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a New Immunosuppressant Histon Deacetylase (HDAC) Inhibitor FR276457 in a Rat Cardiac Transplant Model

Abstract: Histone deacetylase (HDAC) is a known modulator of gene transcription, and the immunosuppressive activity of HDAC inhibitors has been demonstrated in recent several reports. In this study, the HDAC inhibitor FR276457, a hydroxamic derivative, was found to have a similar inhibitory effect on all mammalian HDACs tested, but no isozyme selectivity. Both FR276457 and tacrolimus exerted an immunosuppressive effect on in vitro rat splenocyte proliferation stimulated with Concanavalin A. Next, the effect of FR276457 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Previous studies have demonstrated that HDAC is also actively involved in some inflammatory diseases, 34,35 making these agents hold promise as immunomodulatory drugs. HDACis, such as FR276457 and TSA, have been reported to prolong the median survival time of the transplanted grafts in a rodent animal model as a monotherapy, and even more effective in combination with FK506 or rapamycin, 23,36 which is consistent with our observation in the current study. Obviously, a combination of SAHA and FK506 is more effective than either of them alone in the prevention of allograft rejection, which lead us to explore the pharmacological mechanism of SAHA.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have demonstrated that HDAC is also actively involved in some inflammatory diseases, 34,35 making these agents hold promise as immunomodulatory drugs. HDACis, such as FR276457 and TSA, have been reported to prolong the median survival time of the transplanted grafts in a rodent animal model as a monotherapy, and even more effective in combination with FK506 or rapamycin, 23,36 which is consistent with our observation in the current study. Obviously, a combination of SAHA and FK506 is more effective than either of them alone in the prevention of allograft rejection, which lead us to explore the pharmacological mechanism of SAHA.…”
Section: Discussionsupporting
confidence: 92%
“…111 Coadministration of TSA with subtherapeutic doses of rapamycin for 14 days after transplant boosted regulatory T-cell function, induced allograft tolerance and dramatically improved survival in mouse cardiac and pancreatic islet allograft models. 84 Although similar results have been reported with other panHDACis, 99,112,113 class I-selective HDACis do not appear to augment regulatory T-cell function, 85 turning attention to the role of HDAC6 in this process. It will be interesting to determine whether induction of regulatory T cells contributes to efficacy of HDACis in the settings of heart and renal failure.…”
Section: Antiinflammatory Effects Of Hdacismentioning
confidence: 54%
“…Tao and Hancock [85] have reported that HDAC inhibition promoted the generation of T reg -cells and enhanced their functions. In addition, administration of FR276457, a hydroxamic derivative, can inhibit T-cell proliferation and prolong allograft survival, thereby exhibiting marked immunosuppressive effects in a rat heterotopic cardiac transplant model [86] and in a canine renal transplant model [87]. …”
Section: Hdacs and Immunomodulationmentioning
confidence: 99%